Negotiating Islamic Law and Customary Practice: Fiqh al-Aqalliyyat and Restorative Justice in Banjar Inheritance Disputes - Sarmadi, Ahmad Sukris; Hafidzi, Anwar; Mohlis, Mohlis; Yunin, Oleksandr; Korniienko, Maksym (Jurnal Ilmiah Al-Syir'ah, 2025)
Inheritance disputes in Banjar customary society extend beyond material distribution and are closely connected to kinship relations, moral obligations, and communal harmony. When such disputes are resolved exclusively through state law, particularly the Compilation of Islamic Law (KHI), the outcomes often fail to accommodate the social and cultural realities of indigenous Muslim communities. Formal litigation, with its adversarial structure and procedural rigidity, may intensify conflict rather than restore family relationships. This study adopts a normative legal research design using conceptual, doctrinal, and comparative approaches to examine Banjar customary inheritance mechanisms, namely bacu’ur (genealogical tracing), basuluh (moral and religious consultation), and bapatut (consensus-based deliberation). These mechanisms are analyzed through the perspectives of restorative justice and fiqh al-aqalliyyat as frameworks of contextual Islamic legal reasoning. The analysis relies on primary legal sources, including the 1945 Constitution, the KHI, and legislation on alternative dispute resolution, as well as secondary literature from legal anthropology and restorative justice studies, without employing empirical methods. The findings indicate that the Banjar karakatan system embodies restorative justice principles such as dialogue, collective responsibility, and relational repair. From the perspective of fiqh al-aqalliyyat, these practices constitute legitimate forms of Islamic legal reasoning that prioritize maslahah, islah, and social cohesion within plural legal settings. This study argues that Banjar customary inheritance resolution offers a normatively grounded model for integrating Islamic law, customary practices, and restorative justice within Indonesia’s alternative dispute resolution framework, contributing to broader debates on legal pluralism and the contextual application of Islamic law.